2022
DOI: 10.5194/tc-16-3531-2022
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Global monitoring of snow water equivalent using high-frequency radar remote sensing

Abstract: Abstract. Seasonal snow cover is the largest single component of the cryosphere in areal extent, covering an average of 46 × 106 km2 of Earth's surface (31 % of the land area) each year, and is thus an important expression and driver of the Earth's climate. In recent years, Northern Hemisphere spring snow cover has been declining at about the same rate (∼ −13 % per decade) as Arctic summer sea ice. More than one-sixth of the world's population relies on seasonal snowpack and glaciers for a water supply that is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 226 publications
2
8
0
Order By: Relevance
“…Overall, STC‐MODSCAG fSCA data provide significant, if incremental, additional WSF skill in specific hydroclimatic environments during specific stages of the forecast season, which seems consistent with the notion that no one remotely sensed snow product is universally optimal at this time (Tsang et al., 2022). NRCS operational experience has typically been that long‐lead/early‐season and short‐lead/late‐season forecasts, before substantial winter snowpack accumulation has occurred and after much of the winter snowpack has melted, and when snow cover tends to be patchy, are often challenging for WSF models driven primarily by snow data.…”
Section: Discussionsupporting
confidence: 79%
“…Overall, STC‐MODSCAG fSCA data provide significant, if incremental, additional WSF skill in specific hydroclimatic environments during specific stages of the forecast season, which seems consistent with the notion that no one remotely sensed snow product is universally optimal at this time (Tsang et al., 2022). NRCS operational experience has typically been that long‐lead/early‐season and short‐lead/late‐season forecasts, before substantial winter snowpack accumulation has occurred and after much of the winter snowpack has melted, and when snow cover tends to be patchy, are often challenging for WSF models driven primarily by snow data.…”
Section: Discussionsupporting
confidence: 79%
“…The bias between the altimeter-detected surface and the actual surface can cause an error in the estimated glacier elevation. Specifically, ice surface processes such as blowing snow, firn compaction, surface melting, and refreezing can change the surface scattering properties, leading to elevation measurement errors (Gray et al, 2013(Gray et al, , 2019Hugonnet et al, 2021;Nilsson et al, 2015;Tsang et al, 2022). Previous studies have shown that the penetration effect of radar altimeter data is related to waveform parameters and corrected by a waveform retracking algorithm (Legresy et al, 2005;Nilsson et al, 2015).…”
Section: Potential Error Source Analysismentioning
confidence: 99%
“…Currently, no single method or ensemble of methods has proven capable of measuring SWE to the high standard of accuracy established for global monitoring (Dozier et al, 2016). Recent campaigns, such as the U.S.‐based National Aeronautics and Space Agency (NASA) Snow Experiment (SnowEx; Durand et al, 2018) and the Europe‐based NoSREx and APRESS (Tsang et al, 2022), evaluated a suite of remote sensing approaches (e.g., lidar, radar) for SWE‐mapping applications. At the watershed scale, light detection and ranging (lidar) operations, such as the Airborne Snow Observatory (ASO), have demonstrated operational feasibility (Deems et al, 2013; Painter et al, 2016), but can be cost prohibitive.…”
Section: Introductionmentioning
confidence: 99%
“…backscatter approaches rely on empirical models that are at least partly dependent on the snowpack relative permittivity (Tsang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation